Synthesis and Property Control of Bead-Shaped Silica Adsorbents for Rhodamine B Dye Adsorption - Kim, Jiyull; Yu, Hyeona; Kim, Sang Bin; Kim, Na Yeon; Joo, Ji Bong (The Korean journal of chemical engineering, 2025)
In this study, we synthesized Bead-Shaped Silica and evaluated its performance in adsorbing the dye Rhodamine B. The Bead-Shaped Silica (BS) was synthesized without the use of harmful substances. The BS Adsorbent was synthesized using silica powder and the eco-friendly biopolymer sodium alginate through the Egg box junction method. It was found that by adjusting the molar ratio of silica to alginate during the manufacturing process, the specific surface area and pore size could be controlled. The BS-2.5 sample exhibited the highest surface area and adsorption capacity due to the effective removal of alginate during heat treatment. The pseudo-first-order adsorption kinetic constants and effective diffusivity of the BS material decreased with decreasing pore size, while the adsorption capacity increased. The adsorption behavior of Rhodamine B was modeled using Langmuir and Freundlich isotherms. Based on calculations using these models, the BS-2.5 sample, which had the largest surface area, showed the best performance. Additionally, in continuous flow system experiments, the use of BS resulted in clean water production, whereas columns with silica powder experienced structural damage and dye leakage due to severe pressure drops.